Visualize Scientific Data Using Rational Cubic. - Md. Ali, Jamaludin; Mohd Hassan, Hadibah; Ahmad, Abu Hassan (2004)
Smooth cunrc representation to visualize scientific data is very significant in Computer Graphics and in particular Data Visualization.